Possibilities of processing nepheline raw materials to obtain chemical products (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Sintering of nepheline raw materials with limestone is considered a highly efficient production due to an integrated approach, constant expansion of the range and improvement of the quality of the manufactured products: alumina, soda, potash, white soot and cement. Taking these circumstances into account, a chemical matrix of nepheline raw materials from the Sandyk deposit was compiled and thermodynamic modeling of its destruction with limestone was carried out over wide temperature change ranges. Physicochemical and thermodynamic parameters of the multicomponent system: nepheline-limestone were calculated. The concentration distribution of the main components, active particles and condensed phases at the maximum entropy of the system was established. Temperature limits for the formation and transformation of efficient containing substances of nepheline were revealed.
Keywords: nepheline raw materials, limestone, thermodynamic modeling, entropy